2018
DOI: 10.2471/blt.18.220483
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of national action plans on noncommunicable diseases, Bhutan, Cambodia, Indonesia, Philippines, Sri Lanka, Thailand and Viet Nam

Abstract: By 2016, Member States of the World Health Organization (WHO) had developed and implemented national action plans on noncommunicable diseases in line with the Global action plan for the prevention and control of noncommunicable diseases (2013–2020). In 2018, we assessed the implementation status of the recommended best-buy noncommunicable diseases interventions in seven Asian countries: Bhutan, Cambodia, Indonesia, Philippines, Sri Lanka, Thailand and Viet Nam. We gathered data from a range of published report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…An investigation on 30 State Members of the Organization for Economic Co-operation and Development (OECD) showed these countries have adopted 44 individual policies in three main principles of system strengthening strategies, improved health service delivery, and better population health to tackle NCDs [ 77 ]. Another survey on the implementation of WHO best-buy NCD interventions in seven Asian countries in 2018 found that progress of implemented policies among these countries varied a lot and the significant obstacles of implementation gaps were insufficient funding, limited organizational capacity, inadequate sectoral actions, and a lack of monitoring and evaluation system of policy implementation [ 78 ]. Another survey in India revealed four levels of implementation gap including community level, healthcare facility level, public health system and management level, and policy and research level that need to be handled to combat the NCDs [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation on 30 State Members of the Organization for Economic Co-operation and Development (OECD) showed these countries have adopted 44 individual policies in three main principles of system strengthening strategies, improved health service delivery, and better population health to tackle NCDs [ 77 ]. Another survey on the implementation of WHO best-buy NCD interventions in seven Asian countries in 2018 found that progress of implemented policies among these countries varied a lot and the significant obstacles of implementation gaps were insufficient funding, limited organizational capacity, inadequate sectoral actions, and a lack of monitoring and evaluation system of policy implementation [ 78 ]. Another survey in India revealed four levels of implementation gap including community level, healthcare facility level, public health system and management level, and policy and research level that need to be handled to combat the NCDs [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, civil societies and patient groups can play an essential role in the execution of these measures. 76 Strategies for implementation of behavior changes need to vary based on environmental differences. Data from Western countries suggest that health awareness does not necessarily elicit a shift in behavior, whilst taxation or other incentives may be more successful.…”
Section: Enforcement Of Regulations and Accountabilitymentioning
confidence: 99%
“…For example, the food industry is very influential in many countries and remains a significant barrier to effectively implement and maintain interventions that target unhealthy diets. 76 These industries need to be part of the solution.…”
Section: Enforcement Of Regulations and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity (PA) is associated with several health benefits, including a reduction in risks of several medical conditions and premature mortality [ 1 3 ]. PA is one of the World Health Organization (WHO)'s important aspects in public health [ 4 ]. WHO has launched the Global Action plan on Physical Activity (GAPPA) 2018–2030 to create: (i) active society; (ii) active environments; (iii) active people; and (iv) active systems [ 5 ].…”
Section: Introductionmentioning
confidence: 99%